DAMAGE CAUSED BY PESTS AND DISEASES IN CASSAVA CROPS (REMUNOM, 2024)
Cassava (Manihot esculenta Crantz) is one of the main agricultural crops in several tropical and subtropical regions of the world, playing a crucial role in food security and the economy of many countries. However, cassava production faces significant challenges due to the incidence of pests that affect the plant's development and productivity. This article aims to explore pests and diseases that affect cassava, presenting their impacts, control methods and integrated management strategies, with the aim of providing information in a single location for farmers, students and anyone else interested in the search. for sustainable and effective solutions to protect this vital culture.keyword: Damage, control, integrated pest management, methods and strategies.